Adaptability and Productivity of Forage Crop under Hortipastoral System - Singh, Kundan; Singh, Mukesh; Singh, Atul; Singh , Anuj Kumar; Singh, A. K. (Indian Journal of Extension Education, 2016)
A survey was conducted in Faizabad district of eastern Uttar Pradesh, India was observed that farmers were cultivating  comprehensively fodder crop with horticulture crop to bridge the huge gap between demand and supply of quality feed  and forage required to be narrowed down. Research and development efforts made so far indicated that agroforestry  played an important role in augmenting the supply of fodders especially in sodic land of eastern Uttar Pradesh, which is  estimated to be one third of total area, reported. In order to raise the productivity of forage in more area of sodic land is to  be brought under agroforestry and also cost effective technology is required to be developed. Adaptation of the forage  cropping pattern in these area is very high because the soil structures is not suitable to propagate cash crop. In agro forestry  systems farmers are using the intra spacing of the horticulture trees as under the canopy moisture and shade originate is  suitable for growth and survival of forage crop during summer period. Out of 100 farmers reviewed, Mangifera indica  +Zea mays +Dicanthium annulatum based horticulture system was adopted by majority of farmers in the study area.
Keywords: Hortipastoral system; forage crop; sodic land; productivity and nutritive profile